Role of Cisplatin in Inducing Acute Kidney Injury and Pyroptosis in Mice via the Exosome miR-122/ELAVL1 Regulatory Axis - Zhu, B; He, J; Ye, X; Pei, X; Bai, Y; Gao, F; Guo, L; Yong, H; Zhao, W (Physiological research, 2023)
Although cisplatin is an effective chemotherapy drug for the treatment of various cancers, its clinical use is limited due to its side effects, especially nephrotoxicity. Unfortunately, acute kidney injury (AKI) caused by cisplatin remains one of the main challenges in effective cancer treatment. Evidence increasingly suggests that renal inflammation and pyroptotic inflammatory cell death of renal tubular epithelial cells (RTECs) mainly determine the progression and outcome of cisplatin-induced AKI. However, it is not clear how cisplatin regulates the pyroptosis of RTECs cells in AKI. The current study aimed to determine the regulation mechanism of AKI induced by cisplatin. We used cisplatin to induce AKI in vivo. We performed H&E staining of mouse kidney tissue sections and evaluated serological indicators of kidney injury (including blood urea nitrogen (BUN), serum creatinine, and tumor necrosis factor-alpha (TNF-alpha)). We used immunohistochemistry and western blot to detect the important substrate protein gasdermin D (GSDMD) and key target caspase-1 of pyroptosis, respectively. Cisplatin induced mouse AKI and RTECs pyroptosis. HK2 cell-derived exosomes treated with cisplatin influenced pyroptosis of the surrounding HK2 cells. Cisplatin-treated HK2 cells exosome-derived miR-122 regulated pyroptosis in the surrounding cells. Exosome-derived miR-122 affected cisplatin-induced AKI and HK2 cells pyroptosis by regulating the expression of embryonic lethal abnormal vision (ELAVL1). These results suggest that exosome miR-122 inhibited pyroptosis and AKI by targeting ELAVL1 under cisplatin treatment, and this offers a potential target for the treatment of AKI.
Keywords: Animals; MicroRNAs; Pyroptosis; cisplatina; zvířata; Acute Kidney Injury; Mice; exozómy; pyroptóza; akutní poškození ledvin; Cisplatin; mikro RNA; Exosomes; myši